Care of the Geriatric Colorectal Surgical Patient and Framework for Creating a Geriatric Program: A Compendium From the 2019 American Society of Colon and Rectal Surgeons Annual Meeting. Issue 11 (November 2020) - Saur, Nicole M.; Montroni, Isacco; Shahrokni, Armin; Kunitake, Hiroko; Potenti, Fabio M.; Goodacre, Robert C.; Davis, Bradley R.; Carli, Francesco
Abstract : Supplemental Digital Content is available in the text.